Emergency HeartWare Ventricular Assist Device (HVAD) exchange due to pump thrombosis using minimally invasive technique - Antończyk, Remigiusz; Trejnowska, Ewa; Pacholewicz, Jerzy; Wolny, Tomasz; Nadziakiewicz, Paweł; Antończyk, Karolina; Copik, Izabela; Piontek, Magdalena; Jasińska, Małgorzata; Filipiak, Krzysztof; Głowacki, Maciej; Gawlikowski, Maciej; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Left ventricular assist device (LVAD) thrombosis remains a dreadful complication of mechanical circulatory support, with an incidence of 8–12% depending on the pump type and patient’s comorbidities. Fibrinolysis may be considered early in pump thrombosis, but when contraindicated a pump exchange remains the only alternative. This short report documents an emergency LVAD exchange in a 55-year-old man who underwent LVAD (HeartWare Inc) implantation in 2013 as a bridge to transplantation. Four months after the initial surgery, he suffered from a hemorrhagic stroke despite properly managed anticoagulation. On February 17th, 2017 he was re-admitted with LVAD pump thrombosis. As fibrinolysis was contraindicated, an emergency pump exchange was performed via a limited thoracic incision in order to minimize surgical trauma, reduce intraoperative complications and facilitate immediate post-operative recovery. This report documents the very first LVAD pump exchange as well as the first one performed via a minimally invasive approach in Poland.